High Scale Genomic Applied to B chromosome biology - Ahmad, Syed Farhan (2019)
One of the biggest challenges in chromosome biology is to understand the occurrence and complex genetics of extra, non-essential karyotype elements, commonly known as supernumerary B chromosomes (Bs). Bs are present in diverse species of eukaryotes and their molecular characterization remains elusive for years. A distinguished feature that makes them different from the normal chromosomes (called A chromosomes) is their way of inheritance in irregular fashion. Over the last decades, their genetic composition, function and evolution have remained an unresolved query, although a few successful attempts have been made to address these phenomena. The non-Mendelian inheritance and unpairing/non-recombining abilities make the B chromosomes immensely interesting for genomics studies, thus arising different questions about their genetic composition, survival, maintenance and role inside the cell. This study aims to uncover these phenomena in different species. Here, we sequenced the genomes of three model organisms including fish species Astyanax mexicanus and Astyanax correntinus, and grasshopper Abracris flavolineata with (B+) and without Bs (B-) to identify the B-localized sequences, called B chromosome blocks (“B-blocks”). We established approaches for this analysis that comprised of steps such as comparative genomics analysis and annotation of B chromosomal genes and DNA repeat types. The next generation sequencing (NGS) analyses identified thousands of genes fragments as well as a few complete genes to be present on the Bs. The repetitive DNA analysis showed that the Bs harbor different types of transposable elements (TEs) with domination of Tc1-pogo, hobo-activator and Gypsy DNA transposons, and L2/rex and Jockey retroelements. The functional annotation revealed that the Bs have gained copies of many genes coding for diverse set of functions related to important biological phenomena such as cellular processes, metabolism, development, response to stimulus, immune response, localization, morphogenesis and biological regulation. Our results showed that the Bs are enriched with genes associated to cell cycle and chromosome formation, which might be important for the establishment of Bs in the cell. We further detected different patterns of genomic evolution such as segmental duplications and inversions associated with Bs and highlighted their multi A chromosomal origin. Based on these findings, we corroborate our primary hypothesis that the accumulation of genes on B might have played a key part in driving its transmission, escape, survival and maintenance inside the cell. The B-localized contents, as revealed in our study, provide insights for theories of B chromosome evolution.